Improving The Strategy of Internal Audit institutions In Economic Units under The Changes In The Local and International Environment - AlaaShamsallahNoorullah, Maher Hamid Mohsen, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research problem is that several variables and developments have occurred in the local and international environment that is supposed to affect the reformulation of the strategy and plans of internal audit. So, the reality of internal audit institutions in the research sample was studied to judge how they are affected by these changes and developments and how they prepare their strategy under the criteria. The guidelines of the American Institute of Internal Auditors(IIA)And how they are affected by the variables of thestudy, which include local variables (laws and legislation) and global variables (environmental and technical). As a result, the research recommends adopting international internal audit standards and local and international evidence and guidelines when preparing an internal audit strategy while emphasizing the absorption of advanced internal audit roles, including developing or improving a proactive risk management system in the unit economy.